Art, truth and reality, Cavafy, and cultural studies: A personal perspective. Issue 2 (1st October 2017) - Eleftheriotis, Dimitris
This essay represents a personal and polemical perspective that considers recent cultural and political events in order to reaffirm some of the key principles of cultural studies as a discipline. Particular attention is given to the so-called Cavafy controversy in Greece, and the essay outlines a cultural studies position in relation to it.